Developmental Changes in Executive Functioning - Lee, Kerry; Bull, Rebecca; Ho, Ringo M. H. (Child development, 2013)
Although early studies of executive functioning in children supported Miyake et al.'s (2000) three-factor model, more recent findings supported a variety of undifferentiated or two-factor structures. Using a cohort-sequential design, this study examined whether there were age-related differences in the structure of executive functioning among 6- to 15-year-olds (N = 688). Children were tested annually on tasks designed to measure updating and working memory, inhibition, and switch efficiency. There was substantial task-based variation in developmental patterns on the various tasks. Confirmatory factor analyses and tests for longitudinal factorial invariance showed that data from the 5- to 13-year-olds conformed to a two-factor structure. For the 15-year-olds, a well-separated three-factor structure was found.